PRACTICAL APPLICATION OF WEB-BASED RESOURCES IN THE METHODOLOGICAL TRAINING OF FUTURE ENGLISH TEACHERS - A`zamova Shahnoza Fazliddinovna,; Rustamov Azizbek Utkurovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: The article focuses on the practical application of web-based resources in the methodological training of future English teachers. It examines how digital tools and online platforms can be effectively integrated into teacher education to enhance pedagogical skills and professional competence. Special attention is given to the classification of web-based resources, their role in developing communicative and methodological abilities and their contribution to interactive and student-centered learning environments. The study highlights the importance of online collaboration, autonomous learning, and access to diverse educational materials. It also analyzes modern approaches to incorporating technologies such as learning management systems, multimedia tools and virtual communication platforms into the teaching process.